Penerapan Outdoor Learning Pada Pembelajaran IPAS dalam Mengenal Bagian Tumbuhan Pada Anak Tunagrahita Ringan - Rahma, Azzahra; Devita, Dela; Herlina, Heni (PGSD Universitas Muria Kudus, 2025)
This study aims to improve science learning outcomes (IPAS) by using the outdoor learning method, particularly in recognizing plant parts, for children with mild intellectual disabilities at SLB Pelita Kasih. The research method used is Single Subject Research (SSR) with an A-B-A research design. This design involves three phases: baseline I, intervention, and baseline II. In the baseline I phase, students learn about plant parts without any outdoor learning intervention. Then, in the intervention phase, the outdoor learning method is applied, where students learn outside the classroom by interacting directly with plants. The baseline II phase is conducted to measure the results after the intervention. The study results show a significant improvement in student learning outcomes during the intervention phase compared to the baseline I phase, with an average score of 6 in baseline I, 13.71 during the intervention, and 16.67 in baseline II. The average score in the baseline II phase is higher than in baseline I, confirming the success of this method. By using the outdoor learning method, there is an increase in the understanding of plant parts among students with mild intellectual disabilities through more concrete and interactive learning